Spatial Analysis Applied On Play Area’s Urban Configurations To Enhance The Safety Of Children: Case Of New Urban Pole Of Hamla In Batna - Guedouh, Marouane Samir; Khadraoui, Mohamed Amine; Seraoui, Selma (Journal of Architecture and environment of child, 2024)
This research aims to ensure the safety and develop a socio-cognitive of children in play areas in urban spaces. The concerns about child security have been raised especially in the outdoor urban space of the collective habitat. Nowadays, Risks and dangers are still dominant phenomena that become a parental first preoccupation towards their children, such as Kidnapping, beating, traffic accidents, abuse, addiction...etc. In this regard, several solutions and proposals have been adopted for safer environmental conditions for children. Through the analysis of outdoor urban areas of collective habitat in Hamla districts as a case study, we try to extract what faces of children living in these neighborhoods. Two research techniques are used, the first research technique is an onsite non-participatory observation used to evaluate the urban space organization using the space syntax method. The second research technique used to evaluate urban space organization is the space syntax method. The security system is structured using security smart devices such as surveillance cameras, and alarms… etc., these devices allow a distance parental control of the play areas area and child, while the socio-cognitive system is based on play area space design using digital access and social games. The design of the playgrounds can be easily controlled and used by children using smart technologies for safety. Results demonstrated that the use of smart technology has an imminent impact on the safety and the socio-cognitive development of children in outdoor urban play areas